Influence of physical function and frailty on unplanned readmission in middle-aged and older patients discharged from a hospital: a follow-up study - Sheau-Wen Kan; Hsin-Yen Yen; Mei-Ju Chi; Hao-Yun Huang (Scientific Reports)
Abstract Background: Unplanned readmissions are associated with increased mortality among older patients. This study investigated the effects of changes in physical function and frailty on unplanned readmissions in middle-aged and older patients after discharge. Methods: This longitudinal study recruited participants through convenience sampling from the general wards of a medical center in northern Taiwan. They were aged 50 years or older and identified as being at high risk for readmission or mortality following discharge. Baseline data were collected through interviews conducted the day before discharged, while follow-up data were obtained through interviews at 1, 2, and 3 months post-discharge. Generalized estimating equation (GEE) was used for statistical analysis, incorporating all tracked variables, including physical function and frailty. Results: A total of 230 participants were recruited, each followed three times after discharge. The unplanned readmission rates at 1, 2, and 3 months post-discharge were 2%, 8%, and 14%, respectively. Participants with poorer physical function (odds ratio [OR] = 1.60 [1.27–2.02]) and more severe frailty symptoms (OR = 3.16 [1.45–6.83]) had significantly higher odds of unplanned readmission. The interaction between the time and frailty indicated a significantly lower likelihood of unplanned readmission over time (OR = 0.73 [0.54–0.98]). Conclusions: Declining physical function and frailty are key risk factors for unplanned readmission in older patients. Effective strategies to reduce this risk include monitoring physical function and frailty symptoms and providing supportive care services.